Studies on the Physico-Chemical Properties of Ceramic Tiles Produced from Locally Available Raw Materials (Bangladesh Journal of Scientific and Industrial Research, 2008)
Due to the increasing demand of cost-effective tiles in Bangladesh, using the locally available raw materials five different batches of tiles have been prepared and their physical properties (firing shrinkage, bending strength, water absorption, bulk density etc.) as well as chemical properties were studied in order to evaluate the quality of the products. The present investigation revealed that various properties of the produced tiles are similar to those present in commercial tiles which are available in the local market. Key words: Tiles, Firing shrinkage, Bending strength, Water absorption, Bulk density. DOI: 10.3329.bjsir.v43i1.859Bangladesh J. Sci. Ind. Res. 43(1), 77-88, 2008